(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
Every year, various natural disasters occur around the world. From floods and hurricanes to earthquakes and wildfires, natural disasters can cause significant damage to architecture. Air pollution, earthquakes and droughts are particularly common in Uzbekistan, causing significant damage. The paper presents the experience of studying earthquake risk assessment and seismic resistance of educational institutions in the city of Tashkent, using GIS mapping methods (using the example of schools in the Uchtepa district).